Cradle of Humankind Karsts in Southern Africa - (:unkn) unknown (My University, 2022)
The recent development of karstic and geoarchaeological studies in the karsts of Gauteng, in South Africa, has completely transformed interpretations in these prestigious hominid sites (Sterkfontein, Swartkrans, Kromdraai, Cooper's, Gondolin…). Despite the wealth of faunal and also of hominin fossils, a combination of stratigraphic complexities and dating difficulties kept this region of Africa in the background of evolutionary scenarios for a long time, in particular regarding the emergence of the Homo genus. Indeed, for several decades, the Great East African Rift has been considered as the "cradle of humankind". It has yielded many early hominin fossils, in particular the oldest Australopithecines. These fossils have been well dated thanks to simpler morphosedimentary contexts, which are much easier to reliably date than karstic contexts. The approaches developed by us for more than 15 years in South Africa mobilize various disciplines. On the strength of these, several barriers between disciplines have been broken down and certain dates have been called into question, for example, on intrusive calcite floors that are, in actual fact, much younger than the fossils that they were supposed to date (BRUXELLES et al., 2014). On the basis of this work, new dates place the South African fossils in the same age brackets as the East African fossils. Thus, the dating of the virtually complete Australopithecus fossil StW 563 (Little Foot) gave an age of 3.67 ±0.16 Ma (GRANGER et al., 2015), almost 1.5 Ma older than the dates accepted by the scientific community until then (WALKER et al., 2006). It therefore appears that two regions of Africa, more than 4000 km apart, record a comparable or even parallel evolution, with a similar succession of hominins. The fundamental question raised by these results is therefore whether there are two distinct "cradles of humankind" or whether these two geological traps (the rift and the karst) are only two fragments of a
Keywords: African Research